The Effect of Health Education on Childhood Diarrhea on Knowledge and Anxiety Levels of Parents with Toddlers at Abdul Wahab Syahranie Regional Hospital, Samarinda - Renaldy, Rizal; Bojaxhi, Faruk (Journal of Health Innovation and Environmental Education, 2026)
Purpose of the study: This study aimed to assess the effect of health education on childhood diarrhea on parents’ knowledge and anxiety levels regarding their toddlers, focusing on improving both informational and emotional outcomes in a hospital setting.Methodology: A quasi-experimental design with pretest-posttest was employed involving 50 parents of toddlers admitted to the Melati ward at Abdul Wahab Syahranie Regional Hospital, Samarinda. Data were collected using structured questionnaires for knowledge and a validated anxiety scale. Paired t-tests analyzed pre- and post-intervention scores using SPSS version 25. Ethical approval and informed consent were obtained.Main Findings: The results showed a significant increase in parental knowledge scores from 55.2 ± 8.3 to 82.5 ± 6.2 (p < 0.001). Anxiety levels decreased significantly from 52.4 ± 10.1 to 38.7 ± 7.5 (p < 0.001). Health education effectively enhanced parents’ competence in managing diarrhea and reduced psychological stress, confirming the dual impact of the intervention.Novelty/Originality of this study: This study uniquely integrates both cognitive and emotional outcomes, demonstrating that structured health education simultaneously improves knowledge and reduces anxiety. Unlike previous research focusing only on information, this study highlights the psychosocial dimension of parental support, providing practical insights for hospital-based educational programs and contributing to holistic pediatric care strategies